The Routledge handbook of second language acquisition and language testing - Winke, Paula Marie; Brunfaut, Tineke (The Routledge handbooks in second language acquisition, 2021)
"This Handbook, with 45 chapters written by the world's leading scholars in second language acquisition (SLA) and language testing, dives into the important interface between SLA and language testing: shared ground where researchers seek to measure second language performance to better understand how people learn their second languages. The Handbook also reviews how to best measure and evaluate the second language (L2) learners' personal characteristics, backgrounds, and learning contexts to better understand their L2 learning trajectories. Taking a transdisciplinary approach to research, the book builds upon recent theorizing and measurement principles from the fields of cognitive science, psychology, psycholinguistics, psychometrics, educational measurement, social psychology. The Handbook is divided into six key sections: (1) Assessment concepts for SLA researchers, (2) Building instruments for SLA research, (3) Measuring individual differences, (4) Measuring language development, (5) Testing specific populations, and (6) Measurement principles for SLA researchers. Editors Paula Winke and Tineke Brunfaut have done a sterling job with this Handbook, presenting a comprehensive, transdisciplinary guide to SLA and language testing research. The Handbook will guide both novices and experts toward more reliable and valid second language research, and of factors and components that influence the development of second languages"--Provided by publisher.